Costs and benefits analysis of Aquilaria species on plantation for agarwood production in Malaysia - Mamat, Mohd Farid; Yacob, Mohd Rusli; Lim, Hin Fui; Radam, Alias (Center for Promoting Ideas, 2010)
The establishment of Aquilaria plantation for agarwood production has been regarded by the planters as a green ‘gold mine’ of the future. This study examines the costs and benefits of planting Aquilaria spp. for agarwood production. The analysis shows that whether planting Aquilaria spp. integration with banana (Musa spp.) or planting Aqualaria spp. as a single crop for agarwood production, both options are viable. An investment return for planting Aquilaria spp. integrated with banana (Musa spp.) on 1,000 hectares of land is higher with an internal rate of return (IRR) of 54.85% compared with 38.49% for a single crop Aquilaria plantation. The Net present value (NPV) of investment at a 10% discount for 1,000 hectares integrated planting is RM185.6 million (1 RM=USD0.32 in 2008) while the option involving single crop Aquilaria plantation for agarwood production is RM153.6 million.